2009
DOI: 10.1002/qua.21814
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics simulation on the flexibility and backbone motions of HP1 chromodomain bound to free and lysine 9‐methylated histone H3 tails

Abstract: ABSTRACT:Histone methylation has emerged as a central epigenetic modification with both activating and repressive roles in eukaryotic chromatin. Drosophila HP1 (heterochromatin-associated protein 1) is one of the chromodomain proteins that contain the essential aromatic residues as the recognition pocket for lysine methylated histone H3 tail. The aromatic cage indicates that the complex of chromodomain protein binding lysine methylated histone H3 tail can be seen as a typical host-guest system between protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…Several published macroscopic and CG-mesoscale models of chromatin (23)(24)(25)(26)(27)(28)(29)(30) were able to capture the relevant physicochemical features of DNA and nucleosomes, but, due to inherent limitations, could only approximate histone tails. The interactions and dynamics of modified and unmodified histone tails were recently studied by means of atomistic molecular dynamics (MD) simulations (31,32). A 10 ns MD simulation of HP1 in complex with the K9-trimethylated and S10phosphorylated H3 tail suggested that the two adjacent modifications increase the flexibility of the H3 tail and weaken HP1 binding to chromatin (33).…”
Section: Introductionmentioning
confidence: 99%
“…Several published macroscopic and CG-mesoscale models of chromatin (23)(24)(25)(26)(27)(28)(29)(30) were able to capture the relevant physicochemical features of DNA and nucleosomes, but, due to inherent limitations, could only approximate histone tails. The interactions and dynamics of modified and unmodified histone tails were recently studied by means of atomistic molecular dynamics (MD) simulations (31,32). A 10 ns MD simulation of HP1 in complex with the K9-trimethylated and S10phosphorylated H3 tail suggested that the two adjacent modifications increase the flexibility of the H3 tail and weaken HP1 binding to chromatin (33).…”
Section: Introductionmentioning
confidence: 99%
“…mono-, di-or trimethylated lysines) of the histones. The influence of this cage in the recognition of different stated of methylation in lysine has been mainly studied by classical MD simulations, in a similar fashion to the bromodomain studies described above -most computational work has been performed for the chromodomains.Zhou[127] performed 10 ns molecular dynamics with the AMBER ff03 force field and TIP3P solvation to evaluate the flexibility of the Drosophila heterochromatin-associated protein 1 (HP1) in the free and histone H3 bound states. Zhou found that the free complex is much more flexible than with bound methylated histones.…”
mentioning
confidence: 99%
“…Έλα απιφ παξάδεηγκα πνπ δειψλεη ηνπ ιφγνπ ην αιεζέο είλαη φηη κέρξη πξνζθάησο ε κεζπιίσζε ηεο ηζηφλεο εζεσξείην κία κε αληηζηξεπηή δηεξγαζία, φκσο πξφζθαηεο κειέηεο έδεημαλ ην αληίζεην[119]. Ο Y-K. Jiang θαη ε νκάδα ηνπ δεκνζίεπζαλ 2 εξγαζίεο ζηηο νπνίεο κειέηεζαλ ηελ δηακνξθσηηθή ζπκπεξηθνξά ηεο πξσηεΐλεο θαη ηνπ νιηγνπεπηηδίνπ κε πξνζνκνίσζε κνξηαθήο δπλακηθήο γηα ρξνληθφ δηάζηεκα 10 ns ζην ζχζηεκα ηεο HP1 κε ηελ H3[120,121]. πγθεθξηκέλα έγηλαλ κειέηεο ζε κνλν-θαη ηξηκεζπιησκέλα θαηάινηπα ηεο ιπζίλεο 9 ηεο ηζηφλεο H3 φηαλ βξίζθεηαη καδί κε ηελ HP1.…”
unclassified